2013
DOI: 10.1016/s1995-7645(13)60169-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of ixodid ticks in cattle population of various agro-climatic zones of Punjab, India

Abstract: The findings of the current study would provide a basis for evolving effective control strategy for the management of ticks in bovines of the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 5 publications
5
39
4
Order By: Relevance
“…Ticks are prevalent worldwide from Asia (Haque et al, 2011;Bilkis et al, 2011;Sajid et al, 2011;Razmi and Ramoon, 2012;Singh and Rath, 2013), Africa (Reye et al, 2012;Tiki and Mekonnen, 2011;Elghali and Hassan, 2012), North and South Americas (Guimaraes et al, 2001;Lohmeyer et al, 2011), Australia (Springell, 1974;Kamau, 2011) and Europe (Kirby et al, 2004;Scharlemann et al, 2008). Ticks not only cause direct losses, but also act as vectors for various pathogens of bacterial, rickettsial, protozoal, and viral origin (Petney et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ticks are prevalent worldwide from Asia (Haque et al, 2011;Bilkis et al, 2011;Sajid et al, 2011;Razmi and Ramoon, 2012;Singh and Rath, 2013), Africa (Reye et al, 2012;Tiki and Mekonnen, 2011;Elghali and Hassan, 2012), North and South Americas (Guimaraes et al, 2001;Lohmeyer et al, 2011), Australia (Springell, 1974;Kamau, 2011) and Europe (Kirby et al, 2004;Scharlemann et al, 2008). Ticks not only cause direct losses, but also act as vectors for various pathogens of bacterial, rickettsial, protozoal, and viral origin (Petney et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(B.) microplus from the study region as previously reported by Singh and Rath (2013). Farmers from this area were reported to have high dependence on chemical acaricides particularly SPs and in most cases were being used without maintaining optimum concentrations leading to their inefficacy against tick control.…”
Section: Resultsmentioning
confidence: 58%
“…The results are in agreement with the results of Gattase (1983) in Suez Canal Zone, Darweash (1999) in Elbehaira , Abbas et al, (2006) in Giza and Ismailia, Salim abadi et al, (2010) in Iran and Moges et al, (2012) in Chilga district, northwestern Ethiopia. On the other hand, disagreement with Hassan et al, (1958) in Egypt, El-Housary (1981 in Kafr El-Sheikh governorate and Singh and Rath (2013) in India, who recorded the activity of tick was increasing in the rainy season (autumn and spring) Thus rainfall (humidity) seemed to be an important macroclimatic factor influencing seasonal variation in tick infection.…”
Section: -Discussionmentioning
confidence: 82%